Macroporous Ceramic Filter through Polyurethane Template Replication Method: Characterization and Detergent Wastewater Filtration Trials - Eneng Maryani, S.Si, M.T.; Riska Maspupah; Eko Prabowo Hadisantoso (Balai Besar Keramik, 2020)
Macroporous ceramic filters were made through the template replication method with raw materials, i.e. clay, silica sand and iron oxide powder with a ratio of 70: 27.5: 2.5. The mixture of these ingredients was wet milled in a potmill for 5 hours. Polyurethane as a template was dipped in the mixture slurry with a variation dipping time of 6 and 24 hours. The greenbody filter was calcined at temperature of 900oC with a slowly heating rate. The resulting filter was macroporous with very porous morphology and has interconnections or channels between pores. The pore diameter of the filter which was not added with iron oxide was 1.87 mm and the pore wall was 0.31 mm. The filter added with iron oxide had the highest density and porosity, that is 1.9004 g/cm3 and 38.49%. Filters made of iron oxide powder added material show better filtration performance for pH, TSS and COD parameters for 1% detergent water and detergent wastewater. The best results for the filtration of detergent water samples were pH to 9, TSS reduced by 34.45% and COD decreased by 24.99%.